Per un pugno di libri … scientifici : a divulgation project for high-school students. Issue 1 (1st January 2023) - Burgio, G F; Aramo, C; Cicalò, C; Colalillo, R; Fanti, V; Nannini, A; Pacini, G; Piparo, G; Pirrone, S; Sasso, C; Scotti, V; Serri, G; et al.
Abstract: We discuss the project "Per un pugno di libri … scientifici", aimed at bringing the young generations closer to scientific culture through reading divulgation books about physics. The project, which is addressed to high-school students, is sponsored by INFN and other national and regional research institutions, along with physics departments of some Italian universities.